A survey on 3G mobile network traffic performance and analysis in Ethiopia. Issue 1 (1st January 2022) - Melak Asmare, Fanuel; Mihret Geremew, Fekadu; Getnet Ayalew, Lijaddis
Abstract: Mobile phones have an impact on the economic development of a country as the technology develops through the provision of high-value 3G and 4 G data services accessed via smartphones, tablets, and dongles that deliver mobile data services to businesses and consumers. To be able to fully utilize the resources and to focus on service provision and faster troubleshooting, traffic analysis for the optimization process is of paramount importance. High-quality traces obtained can further be exploited to predict the network load and the network configuration. This can intern be used in re-optimization and other engineering tasks for further improvement of the whole 3G network performance. In this work, 3G packet-switched network traffic had been analyzed based on selected performance indicators. The analysis had compared two 3G radio technologies with respect to cellular mode, time, and geographical locations.